Design and Build a Distance and Heart Rate Monitoring System on a Dynamic Bike Integrated with Power Generating System - Anggara Trisna Nugraha (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2022)
One of the organs of the body that must be protected is the heart. The heart is an organ of the human body that performs important functions to sustain life. Maintaining health is a top priority and requires careful attention, so small abnormalities in the heart can have a big impact on our body's performance [2]. In addition to the rapid development of the field of health sciences, this can affect not only aspects of medicine, but also other supporting fields of science such as chemistry, biology, pharmacy and other scientific fields. Don't forget that informatics plays an important role in maintaining, monitoring, diagnosing, and managing health, especially heart health. With the development of medical science, people are always active in improving their physical fitness in order to remain optimal in the current new normal era. After the Covid-19 pandemic, many things change to adapt to the environment around us. One of the implications of the adjustment in the new normal era is the use of transportation for social distancing. Many people use environmentally friendly and healthy modes of transportation, such as bicycles, to travel. In 2016, Deshmukh and colleagues conducted a study entitled 'Design of a Walking Bike', one of several developments in the title of research that discusses the design of a treadmill bicycle [5]. In this study, a mechanical test and design of a treadmill bicycle was carried out in the form of 3D modeling which had been integrated with a power generating system in the form of adding a BLDC motor to the rear wheel. By following the rapid development of technology. The authors investigated the effect of treadmill cycling on heart rate monitoring using the MAX30102 sensor. The two initial values ​​can easily be derived from the results of the conducted studies. The first test has an error rate of 12.64% and the second test has an error rate of 22.09%. From the results of these tests, the author is in further investigation by adding the Kalman filtering method to the MAX30102 sensor. Then, the output generated from this power generating system can charge the battery up to 12.95 volts with a period of 25 minutes of testing. From the results of these tests, the author is in further investigation by adding the Kalman filtering method to the MAX30102 sensor. Then, the output generated from this power generating system can charge the battery up to 12.95 volts with a period of 25 minutes of testing. From the results of these tests, the author is in further investigation by adding the Kalman filtering method to the MAX30102 sensor. Then, the output generated from this power generating system can charge the battery up to 12.95 volts with a period of 25 minutes of testing.